Diagnosis of Intra-Abdominal Extralobar Pulmonary Sequestration by means of Ultrasound in a Neonate. (20th May 2013) - Pires, Claudio Rodrigues; Czapkowski, Adriano; Araujo Júnior, Edward; Zanforlin Filho, Sebastião Marques
Abstract : Pulmonary sequestration is a congenital abnormality consisting of a mass of pulmonary tissue that presents an abnormal connection with the tracheobronchial tree, with a blood supply coming from an anomalous artery derived from the systemic circulation. Extralobar pulmonary sequestration is characterized by having pleural coverings that are independent of the normal lungs, with vascular supply usually coming from the aorta or from one of its branches. This diagnosis can be suspected prenatally if an abdominal mass, generally below the diaphragm, is seen. Here, we present a case of a neonate on the second day of life, with ultrasonography showing extralobar pulmonary sequestration located above the left adrenal gland that prenatally simulated a neuroblastoma.